If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10n+3(8-8n)=-6(n-4)
We move all terms to the left:
-10n+3(8-8n)-(-6(n-4))=0
We add all the numbers together, and all the variables
-10n+3(-8n+8)-(-6(n-4))=0
We multiply parentheses
-10n-24n-(-6(n-4))+24=0
We calculate terms in parentheses: -(-6(n-4)), so:We add all the numbers together, and all the variables
-6(n-4)
We multiply parentheses
-6n+24
Back to the equation:
-(-6n+24)
-34n-(-6n+24)+24=0
We get rid of parentheses
-34n+6n-24+24=0
We add all the numbers together, and all the variables
-28n=0
n=0/-28
n=0
| -5x+28=-7x+10 | | w/4-9=11 | | 23=4d+5 | | |x+4|=11 | | (-7+9(y+1))=5y+8 | | x+(3x-4)=5-(2x+4) | | t=0.25Y | | x-3/4=13/4 | | (6x-5)-(4x+5)=180 | | 9+4k+7kk=8 | | n*5=15 | | -3x^2+43x+136=0 | | (2x-3)2-42=0 | | X^2=2z | | 3x/2-4=x-6 | | 3(x-4)=2x+4-6x | | x=2/3=5/3 | | 6x-15=x+8=168 | | 6/5+5m/4=69/20 | | 12 – c = 8 | | 4(x+1)+31=3x | | −5+x2=−9 | | 7/26=21/x | | (2x-7)+(3x-23)=80 | | 2(x-1)=3x+2-2x+6 | | 7/3x+6=1/9x | | 4 – 14 = 5x | | (2x-7)+(3x-23)=180 | | 2-4(9y+5)=-7(-6y+3)-7 | | -4(x+2)=10+x-3 | | 3x2-7+2=0 | | 10-15x=0 |